Characterization of MexT, the Regulator of the MexE-MexF-OprN Multidrug Efflux System of Pseudomonas aeruginosa - Köhler, Thilo (American Society for Microbiology, 1999)
We investigated the regulation of the MexEF-OprN multidrug efflux system of Pseudomonas aeruginosa, which is overexpressed in nfxC-type mutants and confers resistance to quinolones, chloramphenicol and trimethoprim. Sequencing of the DNA region upstream of the mexEF-oprN operon revealed the presence of an open reading frame (ORF) of 304 amino acids encoding a LysR-type transcriptional activator, termed MexT. By using T7-polymerase, a 34-kDa protein was expressed in Escherichia coli from a plasmid carrying the mexT gene. Expression of a mexE::lacZ fusion was 10-fold higher in nfxC-type mutants than in the wild-type strain; however, transcription of mexT as well as the mexT DNA region was unchanged. Located adjacent to mexT but transcribed in opposite direction, the beginning of an ORF termed qrh (quinone oxidoreductase homologue) was identified. Expression of a qrh::lacZ fusion was also found to be activated by MexT. Further, we present evidence for coregulation at the transcriptional and the posttranscriptional level between the MexEF-OprN efflux system and the OprD porin responsible for cross-resistance of nfxC-type mutants to carbapenem antibiotics.